Well placement and control optimization for WAG/SAG processes using ensemble-based method. (9th June 2017) - Zhang, Yang; Lu, Ranran; Forouzanfar, Fahim; Reynolds, Albert C.
Abstract : Highlights: The performance of WAG/SAG flooding is greatly improved by the joint optimization. An efficient algorithm combining steepest ascent and the simplex gradient is used. Both simultaneous and sequential approaches for joint optimization are investigated. Well spacing constraints are included in order to keep wells apart. Abstract: Compared to the CO2 flooding, the alternative injection of water/surfactant solution and CO2 gas (WAG/SAG) can provide good control over the mobility ratio, stabilize the displacement front and improve the macroscopic sweep efficiency of the flooding. We show that the performance of a WAG/SAG flood can be significantly improved by optimizing the locations and optimizing rates or pressure in order to avoid gas/water channelling and improve sweep efficiency. To maximize the life-cycle net present value (NPV) for a WAG/SAG process, we implemented a steepest ascent algorithm combined with a simplex stochastic gradient to find the optimal well trajectories and controls. Both simultaneous and sequential approaches for the joint optimization of well locations and controls are investigated for a synthetic channelized reservoir model. Well spacing constraints are also included in the optimization process using the penalty method in order to keep the distance between wells greater than a specified minimum value. Four synthetic reservoir problems are studied and optimized to illustrate the viability of the methodology.